Melhores práticas de gestão e performance da qualidade da informação em projetos de tecnologia da informação sob o efeito moderador de restrições: um survey da experiência brasileira - Rosa, Thatiane de Oliveira (Universidade Federal do Tocantins, 2017)
Proposal – This study aims to assess the influence of best management practices in information quality performance in projects of Information Technology (IT) in restrictions conditions. The study was based on the brazilian experience. Methodology – The survey is backed by a conceptual model, composed of independent variables, moderating variables and dependent variables, which are the best project management practices, criteria for evaluating the quality of information and performance of information quality. To check the conceptual model, at first moment, the search was made in light of the literature. This phase is structured in three stages: 1 - Fundamentals of management of IT projects; 2 - Survey of best practices in project management; 3 - Identification of criteria for evaluating the quality of information and perspectives of information quality performance. In a second step, it was carried out by the group of the best project management practices identified in stage 2, using the statistical method of cluster analysis. Then, a consultation was held with experts to confirm the variables of the conceptual model, as well as presenting the main effects (influences) of best practices in information quality performance, conditioned to moderating variables, namely the criteria for assessing the quality of information. They were selected through technical and scientific criteria, experts with knowledge and experience of the investigated object. Thus, initially they were selected 303 experts with diverse backgrounds Knowledge Areas (Information Technology, Information Systems, Quality of Information, Administration), among others, but these, focusing on Information Technology. The study was based on the brazilian experience in IT projects. Data were collected through a questionnaire of scalar type (Likert) from 1 (lowest intensity) to 5 (highest intensity), with some open questions. And to reduce the subjectivity of the results achieved were applied statistical methods such as the Duncan test, to compare the means, and the Spearman correlation for analysis the influence investigated. Search limitations – The study is aimed at the brazilian experience, therefore, it is recommended applications of the study in other countries. Originality / value – This study stems from a gap in the theoretical clippings about influence best practice in information quality performance in IT projects, particularly in restrictions conditions. Implications for practice management – It is expected that this study will support managers in their decision-making processes in IT projects in dynamic and contingent contexts. It is believed that this represents an increase of value to business ventures.